2008
DOI: 10.1200/jco.2007.15.3312
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Thoracic Radiotherapy for Lung Cancer: A Systematic Review

Abstract: No significant differences were observed for specific symptom-control end points, although improvement in survival favored HD RT. Consideration of palliative thoracic RT of at least 35 Gy(10) BED may therefore be warranted, but must be weighed against increased toxicity and greater time investment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 221 publications
(109 citation statements)
references
References 29 publications
7
100
1
1
Order By: Relevance
“…Subsequently, archived tissue from 77 of 89 randomized patients was analyzed for KRAS mutational status, with the aim of investigating both the effect of KRAS status on treatment outcome and the association between skin toxicity and KRAS status [48]. While escalation of the cetuximab dose resulted in a non-significant trend toward higher RR in wild-type KRAS patients (41.9 vs. 30.4% for the standard dose; p = 0.396), there was a sharp distinction between outcomes according to KRAS status in both treatment arms.…”
Section: Clinical Role Of Kras and Braf Mutationsmentioning
confidence: 99%
“…Subsequently, archived tissue from 77 of 89 randomized patients was analyzed for KRAS mutational status, with the aim of investigating both the effect of KRAS status on treatment outcome and the association between skin toxicity and KRAS status [48]. While escalation of the cetuximab dose resulted in a non-significant trend toward higher RR in wild-type KRAS patients (41.9 vs. 30.4% for the standard dose; p = 0.396), there was a sharp distinction between outcomes according to KRAS status in both treatment arms.…”
Section: Clinical Role Of Kras and Braf Mutationsmentioning
confidence: 99%
“…In the palliative thoracic RT meta -analysis, three trials reported confi rmed cases of myelopathy. Estimates of incidence rates were < 0.5% and did not correlate with RT dose [34] .…”
Section: Central Nervous Systemmentioning
confidence: 97%
“…A meta -analysis of 13 randomized controlled trials evaluating different dosefractionation schedules for palliation of incurable lung cancer included 3473 patients [34] . Dysphagia secondary to esophagitis was the most common acute side effect described, but timing and method of assessment varied.…”
Section: Thoraxmentioning
confidence: 99%
See 2 more Smart Citations